‘He gave us a canvas that was pre-painted and we added to it’ A Qualitative Study to Consider the Outcomes of a Group of Adolescents with Autism Developing a Card Trading Game - Woodhouse, Joanna (2017)
The literature suggests that adolescents with autism experience difficulties in social interaction and understanding. However, interventions to improve socialisation remain under researched. This qualitative case study explores the outcomes of allowing a group of adolescents with autism to develop a card trading game. Three boys and one girl (ages 15-16) participated in the study. Semi-structured interviews, participant observation and consideration of a physical artefact were conducted. Thematic analysis identified three themes: 1) social skills; 2) social reciprocity; and, 3) group dynamics and organisation. Findings show that participant behaviour challenged current theory of Autism Spectrum Condition (ASC) by demonstrating high levels of sustained social interaction and reciprocity. Additionally, unexpected outcomes relating to group organisation, internal structures and contextual norms were displayed. Whilst the focus of the study was unique the pedagogical approaches used may be transferable to other contexts. Creating comfortable social environments and allowing adolescents freedom and agency over their own creativity may have more impact in developing and honing social skills than externally organised programmes of intervention. Recognising the uniqueness of the case this study aims to contribute to the wider discourse on approaches for those working with adolescents with autism. Implications for practice and recommendations for further research are discussed.